CONTEMPORARY CITIZENSHIP - HISTORICAL PREREQUISITES AND PERSPECTIVES - Manov, Boris (Revista Inclusiones, 2019)
The study is conducted through the philosophical-methodological approach of the unity of logical and historical. On this basis, it is argued that the concept of citizenship is a unity of discontinuity and continuity. The discontinuity is expressed in the existence of several historical stages in the concepts of citizenship: antiquity, medieval, modern, and postmodern (“relative discontinuity”). The continuity is ensured by bringing out the “invariant” essence of the concept (and phenomenon) citizenship. That is why the study starts with the presentation of the concept of citizenship in its current, “modern” form and on this basis it is tracked its “becoming” in history.